2004
DOI: 10.1086/426404
|View full text |Cite
|
Sign up to set email alerts
|

A 77-Kilobase Region of Chromosome 6p22.2 Is Associated with Dyslexia in Families From the United Kingdom and From the United States

Abstract: Several quantitative trait loci (QTLs) that influence developmental dyslexia (reading disability [RD]) have been mapped to chromosome regions by linkage analysis. The most consistently replicated area of linkage is on chromosome 6p23-21.3. We used association analysis in 223 siblings from the United Kingdom to identify an underlying QTL on 6p22.2. Our association study implicates a 77-kb region spanning the gene TTRAP and the first four exons of the neighboring uncharacterized gene KIAA0319. The region of asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
337
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(374 citation statements)
references
References 41 publications
(61 reference statements)
24
337
7
Order By: Relevance
“…17,18 Briefly, the Oxford sample included 264 unrelated nuclear families identified from the dyslexia clinic at the Royal Berkshire Hospital in Reading, UK. The majority of families were recruited on the basis of having at least one proband whose single-word reading ability was > 2 s.d.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…17,18 Briefly, the Oxford sample included 264 unrelated nuclear families identified from the dyslexia clinic at the Royal Berkshire Hospital in Reading, UK. The majority of families were recruited on the basis of having at least one proband whose single-word reading ability was > 2 s.d.…”
Section: Subjectsmentioning
confidence: 99%
“…By performing a systematic, highdensity linkage disequilibrium screen of candidate genes within the DYX2 region, we found that variation in the KIAA0319 gene was most strongly implicated in dyslexia susceptibility. Subsequent functional analysis showed that the risk haplotype identified by Francks et al 17 is associated with a reduction of expression of KIAA0319, but does not affect either THEM2 or TTRAP. 19 Two recent studies have indicated that another gene within the DYX2 QTL, DCDC2, may also play a role in developmental dyslexia.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, the identified effect sizes of SNP rs2143340‐ KIAA0319 were reported with opposing risk alleles (Francks et al., 2004; Luciano et al., 2007; Newbury et al., 2011). Contradicting effect size directions of risk alleles were also observed in studies investigating intermediate phenotypes of other diseases: Shulman et al.…”
Section: Discussionmentioning
confidence: 99%